The Effectiveness of Culturally Responsive Teaching-Based E-Motic in Improving The Critical Thinking Skills of Elementary School Students - Dede Mulyana; Yuyun Dwi Haryanti (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effectiveness of *The Effectiveness of Culturally Responsive Teaching-Based E-Motic in Improving The Critical Thinking Skills of Elementary School Students* in improving the critical thinking skills of elementary school students. The study used a quasi-experimental design with a non-equivalent control group design model. The participants involved 60 students in Grade V, who were divided into two groups, namely 30 students in the experimental group and 30 students in the control group, with relatively homogeneous characteristics in terms of age, socioeconomic background, and initial academic achievement. The research instruments included critical thinking ability tests based on indicators of interpretation, analysis, evaluation, inference, explanation, and self-regulation; observation sheets on learning implementation; and student response questionnaires. Data were analyzed using descriptive and inferential statistical tests through independent sample t-tests and effect size calculations. The results showed a significant difference between the experimental group and the control group after treatment (p < 0.05), with a large effect-size category. The increase in critical thinking scores in the experimental group was higher than in the control group across all indicators. In addition, the implementation of learning was in the “very good” category, and the students’ responses to the use of E-MOTIC showed a very positive acceptance rate. These findings indicate that the integration of thematic digital modules with a culturally responsive teaching approach is effective in creating contextual, meaningful learning oriented toward strengthening higher-order thinking skills in primary schools.